An Edge-Minimization Problem for Regular Polygons - Buchholz, Ralph H.; de Launey, Warwick (The Electronic Journal of Combinatorics, 2009)
In this paper we will examine the following problem: What is the minimum number of unit edges required to construct k identical size regular polygons in the plane if sharing of edges is allowed?